2011
DOI: 10.2337/db11-0956
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Tissues Maintain Insulin Sensitivity in Diet-Induced Obesity

Abstract: Reproductive dysfunction is associated with obesity. We previously showed that female mice with diet-induced obesity (DIO) exhibit infertility and thus serve as a model of human polycystic ovary syndrome (PCOS). We postulated that differential insulin signaling of tissues leads to reproductive dysfunction; therefore, a comparison of insulin signaling in reproductive tissues and energy storage tissues was performed. Pituitary-specific insulin receptor knockout mice were used as controls. High-fat diet–induced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…2). Studies in mice have revealed that liver and muscle cells exhibit IR during continuous HI, whereas insulin receptors in pituitary and ovarian cells stay sensitive, an adaptation that increases pituitary hormone secretion and ovarian androgen production [48]. This observation has been used as a model to explain the insulinemic contribution to advanced androgen production and progress to PCOS in women.…”
Section: Excess Insulin Has Multiple Effectsmentioning
confidence: 99%
“…2). Studies in mice have revealed that liver and muscle cells exhibit IR during continuous HI, whereas insulin receptors in pituitary and ovarian cells stay sensitive, an adaptation that increases pituitary hormone secretion and ovarian androgen production [48]. This observation has been used as a model to explain the insulinemic contribution to advanced androgen production and progress to PCOS in women.…”
Section: Excess Insulin Has Multiple Effectsmentioning
confidence: 99%
“…Prior studies by Akamine et al (2) and Nteeba et al (39) established that long exposure to high-fat diet in both rats and mice can lead to a similar reduction in PI3K and Akt phosphorylation in whole ovarian tissue, as seen in the current study compared with lean controls. Results from the present study demonstrate that insulin signaling may be affected by obesity; however, additional studies leveraging insulin challenges or hyperinsulinemic euglycemic clamps are warranted to confirm whether ovaries are insulin resistant in this model (2,66). Studies using primary granulosa cell cultures are also needed to test whether the decrease in PI3K and p-Akt leads to this upregulation of Egr-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, as fertility and corpora lutea numbers were incompletely rescued by pituitary insulin receptor deletion, obesity may have effects at other levels of the reproductive axis. In this regard, the ovary also remains insulin-sensitive in the obese state, and deletion of insulin receptors from ovarian theca interstitial cells also partially rescues obesity-induced infertility (Wu et al, 2013, 2012). The effect of obesity on GnRH neuronal function remains to be investigated.…”
Section: Adult Treatment Models For the Study Of Pcosmentioning
confidence: 99%